The Value Reality of Peace from The Cosmogonic Myth of The Srumbung Gunung Hamlet - Iwan Firman Widiyanto (Syntax Corporation Indonesia, 2022)
This research is based on the idea that myth as a form of culture projects the reality of the values ​​that are lived by the community, talking about collective ideals about the form of society that is dreamed of together. In addition, myth also shows the tendency of people to overcome conflict. This study uses an ethnographic qualitative research method. Thus, the data were taken from direct observations and from interviews with community leaders or elders of the Srumbung Gunung hamlet to find out various versions of the myth of the origin of the Srumbung Gunung hamlet. These data are then analyzed using an ideational cultural framework, exploring the cosmogonic myth of Dusun Srumbung Gunung. Seeing the layers of values ​​that wrap around myth, specifically to understand the values ​​that support peace while at the same time seeing the tendency of community patterns to resolve conflicts. Furthermore, the results of this study show that the reality of the value of peace in myth is prioritizing dialogue or deliberation, cooperation and kinship, respect for nature, respect for those who are different and living an attitude of like to work hard, dare to sacrifice in seeking a prosperous life. This myth also shows the tendency of community patterns in dealing with conflict. There is a tendency for some people to take aggressive actions, but on the other hand there are also those who tend to be more preventive, restrictive and self-defense rather than attack. In the end, a deep understanding of culture is important for peace-building efforts to be more effective.